2022
DOI: 10.1152/ajpendo.00078.2022
|View full text |Cite
|
Sign up to set email alerts
|

Glucagon receptor signaling at white adipose tissue does not regulate lipolysis

Abstract: Although the physiologic role of glucagon receptor signaling in the liver is well defined, the impact of glucagon receptor (Gcgr) signaling at white adipose tissue (WAT) continues to be debated. While numerous studies propose glucagon stimulates WAT lipolysis, we lack evidence that physiological concentrations of glucagon regulate WAT lipolysis. In turn, we performed studies in both wildtype and WAT Gcgr knockout mice to determine if glucagon regulates lipolysis at WAT in the mouse. We assessed the effects of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 79 publications
(105 reference statements)
0
5
0
Order By: Relevance
“…It has been suggested that glucagon increases blood flow, lipolysis, glucose uptake and oxygen consumption in white and BAT 29 31 . Studies in mouse and humans have not revealed a lipolytic effect of glucagon 27 , 32 whereas this may occur in rats 33 . In the present study we found GCGR staining of preadipocytes and BAT, while no WAT was stained, using antibody no.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…It has been suggested that glucagon increases blood flow, lipolysis, glucose uptake and oxygen consumption in white and BAT 29 31 . Studies in mouse and humans have not revealed a lipolytic effect of glucagon 27 , 32 whereas this may occur in rats 33 . In the present study we found GCGR staining of preadipocytes and BAT, while no WAT was stained, using antibody no.…”
Section: Discussionmentioning
confidence: 96%
“…There are ongoing controversies about GCGR expression in adipose tissue 27 . Localization of the GCGR has been reported for both white and BAT 5 , 28 , predominantly based on the identification of GCGR mRNA transcripts 1 , 4 .…”
Section: Discussionmentioning
confidence: 99%
“…In GHdeficient mice however, brown adipose tissue is considerably more metabolically active as mRNA transcripts for key thermogenic and lipolytic genes are significantly elevated, and brown adipose tissue removal normalizes many metabolic features in these mice (Darcy et al, 2016). Increased sensitivity for glucagon in brown adipose or white adipose tissue may also explain the heightened light-cycle lipid oxidation rate we observed, as glucagon receptor activity appears to be dispensable for white-adipose lipolysis (Vasileva et al, 2022), however, the enhanced metabolic rate of brown adipose or white adipose tissue (Darcy et al, 2020) in GH-deficient mice may render physiological relevance to this pathway. Indeed, further study is necessary to determine if glucagon receptor action in adipose tissue is relevant in these animals.…”
Section: Discussionmentioning
confidence: 84%
“… 59 Even though the glucagon receptor was found expressed in adipocytes from rat 60 and human liposarcoma, 61 physiological levels of glucagon did not show an effect on lipolysis in murine WAT. 62 Thus, hepatic glucagon signaling is relying on phosphorylation to mediate fed-state appropriate blood glucose levels, only with peripheral mechanisms acting in adipocytes. Although overall trends in the phosphoproteome agree between SGBS and 3T3-L1 cells, the species and cell line-specific differences seem more pronounced than for the adipocytes acetylomes.…”
Section: Discussionmentioning
confidence: 99%